Covalent organic framework / carbon nanotube composite material, preparation method and application thereof

By combining the covalent organic framework with carbon nanotubes, composite materials for the positive electrode materials of zinc ion batteries were prepared, which solved the problems of poor sustainability of existing material resources and poor electrochemical performance, and achieved zinc ion batteries with high specific capacity and good electrochemical performance.

CN115347179BActive Publication Date: 2025-05-02ANYANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211225645.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-09
Publication Date
2025-05-02
Estimated Expiration
2042-10-09

AI Technical Summary

Technical Problem

The existing zinc ion battery cathode material resources are poor, costly and unsatisfactory electrochemical performance. In particular, the intrinsic conductivity of covalent organic framework materials is low and the utilization of redox activity centers is limited.

Method used

A covalent organic framework/carbon nanotube composite material is used to form a composite material by combining melamine and melamine acid with carbon nanotubes, and is used for the positive electrode material of zinc ion battery. The method includes uniformly dispersing the carbon nanotubes in a melamine solution, then adding melamine acid, carrying out reaction and solid-liquid separation, washing and drying to prepare a composite material with high conductivity and good stability.

Benefits of technology

The specific capacity and electrochemical performance of zinc ion batteries have been improved, and the discharge specific capacity can reach 791mAh/g, which is far higher than the specific capacity of a simple covalent organic skeleton electrode material, and the material cost is low and the resource sustainability is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 221009141020
    Figure 221009141020
  • Figure 221009141023
    Figure 221009141023
  • Figure 221009141028
    Figure 221009141028
Patent Text Reader

Abstract

The present invention relates to a method for preparing a covalent organic skeleton / carbon nanotube composite material, comprising the following steps: 1) dissolving melamine powder in an organic solvent to obtain solution A, and then uniformly dispersing carbon nanotube powder in solution A to obtain system A; 2) dissolving cyanuric acid in an organic solvent to obtain solution B; 3) adding solution B to system A for reaction, and then subjecting to solid-liquid separation, washing, and drying treatment to obtain the system A. The material of the present invention can be used as a positive electrode material for zinc ion batteries, and can exert the synergistic effect of melamine cyanuric acid covalent organic skeleton and carbon nanotubes, thereby improving the electrochemical energy storage characteristics of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a covalent organic skeleton / carbon nanotube composite material, a preparation method and application thereof. Background Art

[0002] Due to Zn 2+ / Zn has low redox potential (-0.76V relative to standard hydrogen electrode), high theoretical energy density (820mAh / g), good cycle stability, low cost, high safety and other advantages, making secondary aqueous zinc batteries have good development prospects in the new generation of energy storage devices. At present, the positive electrode materials of zinc-ion batteries are mainly inorganic compounds such as metal oxides and Prussian blue analogs, but these materials have disadvantages such as poor resource sustainability and high cost.

[0003] In recent years, organic electrode materials have attracted much attention due to their advantages such as low cost, structural diversity, strong designability and redox reversibility. Among them, the electronic conductivity of small organic molecular materials is usually poor, and the charged functional groups inevitably dissolve in polar aqueous electrolytes, which usually leads to unsatisfactory electrochemical performance of the battery. Covalent organic frameworks are versatile crystalline porous solid materials that form well-defined two-dimensional or three-dimensional frameworks by connecting organic precursors with covalent bonds. Compared with small organic molecules, covalent organic framework materials are generally insoluble in organic solvents and aqueous solutions and have better stability in electrolytes. In addition, the large π-electron conjugated configuration gives them better electronic conductivity. However, the intrinsic conductivity of covalent organic framework materials is still low, and the utilization of their redox active centers is often limited, resulting in poor electrochemical performance. Summary of the invention

[0004] The present invention aims to overcome the defects of the prior art and to provide a covalent organic skeleton / carbon nanotube composite material. The preparation method of the composite material is simple and the raw materials used are cheap and readily available. The composite material is applied to aqueous zinc ion batteries and has a high battery capacity and good electrochemical performance.

[0005] The present invention also provides a preparation method of the covalent organic skeleton / carbon nanotube composite material and its application in aqueous zinc ion batteries.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a covalent organic framework / carbon nanotube composite material comprises the following steps:

[0008] 1) dissolving melamine powder in an organic solvent to obtain solution A, and then uniformly dispersing carbon nanotube powder in solution A to obtain system A;

[0009] 2) dissolving cyanuric acid in an organic solvent to obtain solution B;

[0010] 3) adding solution B into system A to react, and then performing solid-liquid separation, washing and drying to obtain a covalent organic framework / carbon nanotube composite material.

[0011] Specifically, in step 1), 0.2-5.0 g of melamine can be dissolved in 15-60 mL of an organic solvent; to accelerate the dissolution of melamine, the temperature can be heated to 20-80° C. and stirred to dissolve. The amount of carbon nanotube powder used is 0.1-3 g, and ultrasonic treatment can be performed for 0.5-1 hour to uniformly disperse the carbon nanotube powder.

[0012] Specifically, in step 2), 0.2-5.0 g of cyanuric acid can be dissolved in 10-60 mL of an organic solvent. To accelerate the dissolution of cyanuric acid, the temperature can be heated to 20-80° C. and stirred to dissolve.

[0013] Specifically, in step 1) and step 2), the organic solvent may be methanol, formaldehyde, acetonitrile, pyridine or dimethyl sulfoxide.

[0014] Specifically, in step 3), the reaction temperature may be 20-80° C., and the reaction time may be 1-24 h; and the drying treatment may be vacuum drying at 50-70° C. for 24±12 h.

[0015] The present invention provides a covalent organic skeleton / carbon nanotube composite material prepared by the above method, namely, a melamine-cyanuric acid (MCA) / carbon nanotube (CNTs) composite material.

[0016] The present invention also provides the use of the covalent organic skeleton / carbon nanotube composite material as a positive electrode material for an aqueous zinc ion battery.

[0017] For the above application, specifically, the positive electrode preparation method is as follows: the covalent organic framework / carbon nanotube composite material, the conductive agent, and the binder are mixed in the presence of a solvent to form a slurry, which is then evenly coated on the current collector and vacuum dried at 80-100°C for 20-30h to form a positive electrode sheet.

[0018] Furthermore, the conductive agent may be one or more of carbon black, acetylene black, microcrystalline graphite, etc.; the binder may be one or two of polytetrafluoroethylene or polyvinylidene fluoride, etc.; the current collector may be one of titanium mesh, titanium foil, titanium sheet, stainless steel mesh, stainless steel foil, carbon rod, etc.

[0019] In the above application, when assembling an aqueous zinc ion battery, the negative electrode can be a metal zinc sheet, zinc powder, zinc wire or a material containing metal zinc, and the electrolyte is an inorganic salt aqueous solution containing divalent zinc ions such as zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, or zinc chloride with a concentration of 2 mol / L.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The raw materials used in the preparation of the melamine-cyanuric acid (MCA) / carbon nanotube (CNTs) composite material of the present invention are all conventional drugs, with low cost, and the preparation process is simple and easy to operate, and is easy to industrialize. Compared with inorganic electrode materials, it has the advantages of resource sustainability, environmental friendliness, and diverse structures;

[0022] 2) Compared with traditional zinc-ion batteries, the abundant C=O and C=N groups in MCA covalent organic framework materials can well react with Zn 2+ Coordination is beneficial to the insertion / deintercalation of zinc ions during the charge and discharge process of zinc ion batteries, thereby increasing the specific capacity of the battery. MCA and CNTs are used as positive electrode materials for zinc ion batteries after being combined, which can solve the defect of low electronic conductivity of MCA itself, give play to the synergistic zinc storage effect of the two, and obtain enhanced electrochemical energy storage characteristics. Under the condition of 0.01A / g, the discharge specific capacity of the battery positive electrode material can be as high as 791mAh / g, which is much higher than the specific capacity of the pure MCA electrode material (169mAh / g). BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope photo of the MCA / CNTs composite material prepared in Example 1 of the present invention; the left picture is a scanning electron microscope photo at a magnification of 25,000 times, and the right picture is a scanning electron microscope photo at a magnification of 50,000 times;

[0024] Figure 2 This is a Fourier infrared spectrum of the MCA / CNTs composite material prepared in Example 1 of the present invention;

[0025] Figure 3 This is a constant current charge and discharge curve diagram of an aqueous zinc ion battery at a current density of 0.01 A / g for the MCA / CNTs composite electrode material and the pure MCA electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0027] Example 1

[0028] The present invention will now be further described in detail in conjunction with specific embodiments and the accompanying drawings. The following embodiments may enable those skilled in the art to more fully understand the present invention, but these embodiments are not intended to limit the scope of protection of the present invention. "One embodiment" or "embodiment" referred to herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. "In one embodiment" appearing in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0029] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Room temperature refers to 25±5°C.

[0030] In the following embodiments, the raw materials used are all common commercially available products that can be purchased directly, for example, multi-walled carbon nanotubes were purchased from Kaisa (Guangdong) New Materials Co., Ltd.

[0031] Example 1

[0032] A method for preparing a covalent organic framework / carbon nanotube composite material comprises the following steps:

[0033] Step 1: Weigh 0.50 g of melamine powder and add it to 20 mL of dimethyl sulfoxide (DMSO), which can be slightly heated to about 40°C, add a magnet and place it in a magnetic stirrer to make it dissolve quickly under stirring, which is recorded as solution A; add 0.12 g of multi-walled carbon nanotube powder to solution A, and ultrasonicate for 30 minutes to evenly disperse the carbon nanotube powder to obtain system A;

[0034] Step 2: Weigh 0.50 g of cyanuric acid and dissolve it in 10 mL of DMSO. Slightly heat it to about 40°C, add a magnet and place it in a magnetic stirrer to allow it to dissolve quickly under stirring. This is called solution B.

[0035] Step 3: Slowly add solution B into system A, cover with plastic wrap and react under magnetic stirring at room temperature for 12 h;

[0036] Step 4: After the stirring reaction is completed, filter and wash with DMSO for 4 times, and finally dry in an electric constant temperature forced air drying oven at 60°C for 24 h. The obtained product is recorded as MCA / CNTs composite material.

[0037] Figure 1 The following is a scanning electron microscope photo of the MCA / CNTs composite material prepared in this example. The MCA is in granular form and is located in the conductive network composed of CNTs, indicating that the MCA is in situ grown on the CNTs. The conductive network composed of CNTs significantly improves the conductivity of MCA / CNTs, making full use of the active sites of MCA.

[0038] Figure 2 This is the Fourier infrared spectrum of the MCA / CNTs composite material prepared in this example. -1 The characteristic peak appears at 1660 cm -1 The characteristic peak appears at the position of -C=N, indicating that the target product has the same 2+ Active site for coordination.

[0039] Comparative Example 1

[0040] A method for preparing a covalent organic framework composite material comprises the following steps:

[0041] Step 1: Weigh 0.50 g of melamine powder and add it to 20 mL of dimethyl sulfoxide (DMSO), which can be slightly heated to about 40°C. Add a magnet and place it in a magnetic stirrer to allow it to dissolve quickly under stirring. This is referred to as solution A.

[0042] Step 2: Weigh 0.50 g of cyanuric acid and dissolve it in 10 mL of DMSO. Slightly heat it to about 40°C, add a magnet and place it in a magnetic stirrer to allow it to dissolve quickly under stirring. This is called solution B.

[0043] Step 3: Slowly add solution B into solution A, cover with plastic wrap and stir magnetically at room temperature for 12 h;

[0044] Step 4: After the stirring is completed, the mixture is filtered and washed with DMSO for 4 times, and finally dried in an electric constant temperature blast drying oven at 60°C for 24 h. The obtained product is recorded as MCA material.

[0045] Example 2

[0046] A method for preparing a covalent organic framework / carbon nanotube composite material comprises the following steps:

[0047] Step 1: Weigh 0.80 g of melamine powder and add it to 25 mL of dimethyl sulfoxide (DMSO), which can be slightly heated to about 40°C, add a magnet and place it in a magnetic stirrer to make it dissolve quickly under stirring, which is recorded as solution A; add 2 g of multi-walled carbon nanotube powder to solution A, and ultrasonicate for 30 minutes to evenly disperse the carbon nanotube powder to obtain system A;

[0048] Step 2: Weigh 0.80 g of cyanuric acid and dissolve it in 15 mL of DMSO. Slightly heat it to about 40°C, add a magnet and place it in a magnetic stirrer to allow it to dissolve quickly under stirring. This is called solution B.

[0049] Step 3: Slowly add solution B into system A, cover with plastic wrap and react with magnetic stirring at 60°C for 12 h;

[0050] Step 4: After the stirring reaction is completed, filter and wash with DMSO for 4 times, and finally dry in an electric constant temperature forced air drying oven at 60°C for 24 h. The obtained product is recorded as MCA / CNTs composite material.

[0051] Application test

[0052] The MCA / CNTs composite material prepared in Example 1 is applied to an anode material of an aqueous zinc ion battery, which comprises the following steps:

[0053] Step a: According to the mass ratio of MCA / CNTs composite material: acetylene black: polyvinylidene fluoride = 8:1:1, 0.4 g, 0.05 g, and 0.05 g of the corresponding substances were weighed respectively, mixed and placed in a 10 mL weighing bottle, 40 ml of N-methylpyrrolidone was added dropwise to the bottle, and a magnetic stirrer was placed in the bottle for 24 hours to obtain slurry A;

[0054] Step b: Use a four-sided coating device (100 um) to evenly coat the prepared slurry A on a separate titanium sheet. Vacuum dry at 60° C. for 24 hours to obtain a positive electrode sheet of the battery;

[0055] Step c: Using a metal zinc sheet as the negative electrode and a 2 mol / L zinc sulfate solution as the electrolyte, an aqueous zinc ion battery is assembled.

[0056] Referring to the above method, the MCA material prepared in Comparative Example 1 was applied to the anode material of an aqueous zinc ion battery, and an aqueous zinc ion battery was produced.

[0057] Figure 3 The constant current charge and discharge curve of the low-temperature aqueous zinc ion battery assembled with the MCA / CNTs composite material obtained in Example 1 and the pure MCA material at a current density of 0.01A / g is given. Figure 3 It can be seen that the discharge capacity of the low-temperature aqueous zinc-ion battery assembled with the MCA / CNTs composite material can be as high as 791 mAh / g, which is much higher than the capacity of the low-temperature aqueous zinc-ion battery assembled with the simple MCA material (169 mAh / g). This shows that the MCA / CNTs composite material of the present invention has great application potential.

[0058] In summary, the covalent organic framework / carbon nanotube composite material prepared by the present invention has excellent performance when applied to positive electrode materials of aqueous zinc ion batteries and is worthy of promotion and application.

[0059] Based on the above-mentioned ideal embodiment of the present invention, through the above-mentioned description, relevant staff can make various changes and modifications without departing from the technical concept of the present invention. Any changes and deformations of various other applications made according to the technical concept of the present invention should be included in the protection scope of the patent requirements of the present invention.

Claims

1. Application of a covalent organic framework / carbon nanotube composite material as a positive electrode material for an aqueous zinc ion battery, characterized in that: The covalent organic framework / carbon nanotube composite material is prepared by the following steps: 1) dissolving melamine powder in an organic solvent to obtain solution A, and then uniformly dispersing carbon nanotube powder in solution A to obtain system A; 2) dissolving cyanuric acid in an organic solvent to obtain solution B; 3) Add solution B into system A to react, and then perform solid-liquid separation, washing and drying to obtain the product; In step 1), 0.2-5.0 g of melamine is dissolved in 15-60 mL of an organic solvent; the amount of carbon nanotube powder used is 0.1-3 g; In step 2), 0.2-5.0 g of cyanuric acid is dissolved in 10-60 mL of an organic solvent.

2. The use of the covalent organic framework / carbon nanotube composite material as claimed in claim 1 as a positive electrode material for aqueous zinc ion batteries, characterized in that: In step 1) and step 2), the organic solvent is methanol, formaldehyde, acetonitrile, pyridine or dimethyl sulfoxide.

3. The use of the covalent organic framework / carbon nanotube composite material as claimed in claim 1 as a positive electrode material for aqueous zinc ion batteries, characterized in that: In step 3), the reaction temperature is 20-80°C, the reaction time is 1-24h; and the drying treatment is vacuum drying at 50-70°C for 24±12h.

4. The use of the covalent organic framework / carbon nanotube composite material as claimed in claim 1 as a positive electrode material for aqueous zinc ion batteries, characterized in that: The positive electrode preparation method is as follows: the covalent organic framework / carbon nanotube composite material, the conductive agent, and the binder are mixed in the presence of a solvent to form a slurry, which is then evenly coated on the current collector and vacuum dried at 80-100°C for 20-30h to form a positive electrode sheet.

5. The use of the covalent organic framework / carbon nanotube composite material as a positive electrode material for aqueous zinc ion batteries as claimed in claim 4, characterized in that: The conductive agent is one or more of carbon black, acetylene black, and microcrystalline graphite; the binder is one or two of polytetrafluoroethylene and polyvinylidene fluoride; and the current collector is one of titanium mesh, titanium foil, titanium sheet, stainless steel mesh, stainless steel foil, and carbon rod.

6. The use of the covalent organic framework / carbon nanotube composite material as claimed in claim 1 as a positive electrode material for aqueous zinc ion batteries, characterized in that: When assembling an aqueous zinc ion battery, the negative electrode is a metal zinc sheet, zinc powder or zinc wire, and the electrolyte is zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate or zinc chloride with a concentration of 2 mol / L.